Electrophoretic-deposited MXene titanium coatings in regulating bacteria and cell response for peri-implantitis - Huang, Si; Fu, Yu; Mo, Anchun (Frontiers in Chemistry, 2022)
Background: Two-dimensional（2D）MXenes have continued to receive increasing interest from researchers due to their graphene-like properties, in addition to their versatile properties for the applications in electronic devices, power generation, sensors, drug delivery, and biomedicine. However, their construction and biological properties as titanium coatings to prevent peri-implantitis are still unclear. Materials and methods: In this work, few-layer Ti3C2Tx MXene coatings with different thicknesses at varied depositing voltages (30V, 40V and 50V) were constructed by anodic electrophoretic deposition without adding any electrolytic ions. In vitro cytocompatibility assay was performed on preosteoblasts (MC3T3-E1) cell lines after the characterization of the coating. Meanwhile, the antibacterial activity against bacteria which are closely related to peri-implantitis including Staphylococcus aureus (S. aureus) and its drug-resistant strain MRSA were further investigated. Results: MXene-coated titanium models with different thicknesses were successfully assembled by analyzing the results of characterization. The compounding of Ti3C2Tx could significantly improve the initial adhesion and proliferation of MC3T3-E1 cells. Moreover, the coating can effectively inhibit the adhesion and cell activity of S. aureus and MRSA, and MRSA expressed greater restricting behavior than S. aureus. The ability to promote antibacterial activity is proportional to the content of Ti3C2Tx. And its antioxidant capacity to reduce ROS in the culture environment and bacterial cells was firstly reveled. Conclusion: In summary, this work shows a new avenue for MXene-based nanobiomaterials under the clinical problem of multiple antibiotic resistance.